Phase II Study of Intravenous Etoposide in Patients with Relapsed Ependymoma (CNS 2001 04). Issue 1 (13th April 2022) - Apps, John R; Maycock, Shanna; Ellison, David W; Jaspan, Timothy; Ritzmann, Timothy A; Macarthur, Donald; Malluci, Conor; Wheatley, Keith; Veal, Gareth J; Grundy, Richard G; Picton, Susan
Abstract: Background: Relapsed ependymoma has a dismal prognosis and the role of chemotherapy at relapse remains unclear. This study prospectively evaluated the efficacy of intensive intravenous etoposide in patients less than 21 years of age with relapsed intra-cranial ependymoma(NCT00278252). Procedure: Single arm, phase II trial using Gehan's two-stage design. Patients received intravenous etoposide 100mg/m2 on Days 1-3, 8-10, and 15-17 of each 28 day cycle, up to maximum of six cycles. Primary outcome was radiological response after three cycles. Pharmacokinetic analysis was performed in 10 patients. Results: 25 patients were enrolled and included in the intention to treat (ITT) analysis. Three patients were excluded in per protocol analysis (PP). After three cycles of etoposide, 5 patients (ITT 20%/PP 23%) had a complete response (CR), partial response (PR) or objective response (OR). 9 patients (ITT 36%/PP 41%, ) had a best overall response of CR, PR or OR. 1 year PFS was 24% in ITT and 23% in PP populations. 1 year OS was 56% and 59%, 5 yr OS was 20% and 18%, respectively in ITT and PP populations. Toxicity was predominantly haematological, with 20/25 patients experiencing a grade 3 or higher haematological adverse event. Conclusions: This study confirms activity of IV etoposide against relapsed ependymoma, however this is modest, not sustained and similar to that with oral etoposide, albeit with increased toxicity. These results confirm the dismal prognosis in this disease, provide a rationale to include etoposide within drug combinations and highlight the need to develop novel treatments for recurrent ependymoma.